Hubungan status gizi, umur, dan jenis kelamin dengan derajat infeksi dengue pada anak - Arafah, Siti Nurbyan; Herlina, Nina; Dharmawan, Akhmad Kheru; Pinilih, Astri (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and remains a major health problem in Indonesia, especially among children. The severity of dengue infection is thought to be influenced by nutritional status, age, and gender, but previous studies have shown varying results. Purpose: To determine the relationship between nutritional status, age, and gender and the severity of dengue infection in children. Method: This study used an observational analytical design with cross-sectional proximity. The sample consisted of 140 children diagnosed with dengue infection at Dr. H. Abdul Moeloek Regional Hospital in 2023 and who met the inclusion criteria. Secondary data were obtained from medical records and analyzed using the Chi-Square test to determine the relationship between variables and the severity of dengue infection. Results: Bivariate analysis showed no association between age and the severity of dengue infection (p=0.219), gender and the severity of dengue infection (p=0.360), or nutritional status and the severity of dengue infection (p=0.292). Conclusion: There is no significant relationship between age, gender, and nutritional status and the severity of dengue infection in children.   Keywords: Age; Dengue Hemorrhagic Fever; Degree of Dengue Infection; Gender; Nutritional Status.   Pendahuluan: Demam Berdarah Dengue (DBD) merupakan penyakit infeksi yang disebabkan oleh virus dengue dan masih menjadi masalah Kesehatan utama di Indonesia, khususnya pada anak-anak. Tingkat keparahan infeksi dengue diduga dipengaruhi oleh faktor status gizi, umur, dan jenis kelamin, namun hasil penelitian sebelumnya menunjukan hasil yang bervariasi. Tujuan: Untuk mengetahui hubungan status gizi, umur, dan jenis kelamin dengan derajat infeksi dengue pada anak. Metode: Penelitian ini menggunakan desain analitik observasional dengan pendekatan cross-sectional. Sampel penelitian adalah 140 anak yang terdiagnosa infeksi dengue di RSUD Dr. H. Abdul Moeloek Tahun 2023 dan memenuhi kriteria inklusi. Data sekunder diperoleh dari data rekam medis, kemudian dianalisis menggunakan uji Chi-Square untuk mengetahui hubungan antar variabel dengan derajat infeksi dengue. Hasil: Analisis bivariat menunjukan tidak terdapat hubungan antara umur dengan derajat infeksi dengue (p=0.219), jenis kelamin dengan derajat infeksi dengue (p=0.360), maupun status gizi dengan derajat infeksi dengue (p=0.292). Simpulan: Tidak ada hubungan yang signifikan antara umr, jenis kelamin, dan status gizi dengan derajat infeksi dengue pada anak.   Kata Kunci: Demam Berdarah Dengue; Derajat Infeksi Dengue; Jenis Kelamin; Status Gizi;  Umur.